The Existence of the Government in Taking Over the Haruku Island Area for the Conduciveness of Local Communities in Maluku Province - Tomi Khoyron Nasir; Daya Nur Pratama; Atik Winanti (JURNAL HUKUM SEHASEN, 2023)
The existence of the Indonesian government in the context of administering Maluku provincial government is clearly very important and strategic for the Maluku people, especially the Sasi indigenous people in the Central Maluku region. The desire of the people of Central Maluku to maintain the conduciveness of its citizens is very dependent on two factors, namely security factors and economic factors, but between these two factors, the security factor is the most important thing needed by the people of Central Maluku. The existence of the government to take over the Haruku island area completely and exclusively can provide good results in obtaining regional income for Central Maluku in order to increase the sense of justice, security of the indigenous people as well as the welfare of the Sasi Indigenous family and community in the Haruku region, Maluku. The research method used in this research is the empirical juridical method. The research results show that the existence of the Indonesian Government in taking over the Haruku island region has resulted in peace for the culturally heterogeneous Haruku residents as well as high profits for the Sasi indigenous people in the Haruku region, Central Maluku where regional income can be felt by all local communities. The hope for the future with the presence of the Indonesian government is to create a sense of security for the indigenous people of Sasi, Haruku, Central Maluku in managing natural resource products in the future, so as to achieve development and exploitation towards good economic prospects for the people of Maluku province.